Fountain Water as a Source of Opportunistic Escherichia coli and Aeromonas hydrophila Strains in Atmospheric Air - Iwona Gołaś; Anna Gotkowska-Plachta (Aerosol and Air Quality Research)
Abstract The aim of this study was to determine the effect of fountain water on the contamination of atmospheric air with opportunistic Escherichia coli and Aeromonas hydrophila, and to evaluate the resulting health risks to humans. The counts of bacteria, their resistance to eight antibiotics, the multiple antibiotic resistance (MAR) index, and the minimum inhibitory concentrations (MICs) of ciprofloxacin (CIP) and tetracycline (TE) were determined in samples of air collected in the immediate vicinity of fountains (A0) and at a distance of 20 m (A20), and in samples of water (W) collected from five fountains. The counts of E. coli and A. hydrophila were highest in bioaerosols (A0), and they were 10–100 times lower in A20 samples. Most E. coli and A. hydrophila strains isolated from air samples were resistant to CIP, TE, ampicillin (AMP), and trimethoprim/sulfamethoxazole (SXT), and 6.7–46.2% of the isolates exhibited multidrug resistance. The values of the MAR index were high in all air samples and similar to those noted in fountain water isolates (0.86–0.87). In total, 17–75% of E. coli and A. hydrophila strains isolated from A0 and A20 samples were resistant to high doses of CIP and TE. Agglomerative clustering revealed five clusters of strains isolated from atmospheric air (A0, A20) and fountain water. The results indicate that fountains can be a source of atmospheric air contamination with potentially pathogenic E. coli and A. hydrophila bacteria.